The Influence of TOCOMSION Media on Prosocial Behavior for Children 5-6 Years Old - Isme, Ester Gabriella; Anggraini, Kristin (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2025)
This study analyses the effect of TOCOMSION media on the prosocial behaviour of children aged 5-6 years at Creative Excellent Children Kindergarten. Based on empirical studies, some children have difficulty sharing, cooperating, and showing empathy. One of the causes is a less interactive learning method. This study used the True Experimental Design method with pretest-posttest control group. The sample consisted of 25 children who were divided into experimental and control groups. Data were collected through observation and tests, then analysed using the Mann-Whitney U test. The results showed that TOCOMSION significantly improved prosocial behaviour, especially in the aspects of cooperation, sharing, and empathy. This happens because TOCOMSION integrates physical activities and social interactions that encourage children to work together and control emotions. Through repeated treatment, it is shown that TOCOMSION media has a significant effect on prosocial behaviour. In conclusion, TOCOMSION is effective in improving children's prosocial behaviour through interactive and fun learning. The implication is that this media can be an alternative for PAUD teachers to develop children's social-emotional skills. Enhancing children's learning experience is more interactive and fun, while developing social-emotional skills that are important for their future